The cinematographic representation of HIV/aids: Analysis of the films released between 1981 and 1991 - López-Martín, Álvaro (Revista Española de Comunicación en Salud, 2019)
The mass media have always had a great influence on the construction of public opinion. This has been demonstrated with any major contemporary problem, such as HIV / AIDS, whose presence in the films has served to raise awareness and image about the human immunodeficiency virus (HIV). This work aims to know how HIV is represented in the films released between 1981 and 1991. That is, during the first decade since the identification of the first clinical case of this virus. For this, four productions have been analyzed: An Early Frost, Parting Glances, The Fly and Longtime Companion. The analysis of the content of these films has allowed us to determine how HIV was presented. On the one hand, from the social perspective, it was observed that in all the films the fears and prejudices towards said virus become visible. In addition, HIV was associated (almost) only with the gay community. In contrast, it could be seen that the medical procedures and the forms of HIV transmission shown were correct, with greater precision and realism in the films released in the final years of the analysis period.